Potential of 2, 4-Dihydroxybenzoic Acid as an Oviposition Stimulant for Mass-Reared Ladybird Beetles. Issue 2 (7th March 2019) - Riddick, E W; Wu, Z; Eller, F J; Berhow, M A
Abstract: The discovery of inexpensive, readily available bioflavonoids, and their degradation products that boost the reproductive potential of mass-reared predators is the overarching goal of this research. We tested the hypothesis that 2, 4-dihydroxybenzoic acid (DHBA), an inexpensive degradation product of morin (a flavonol bioflavonoid), stimulates oviposition by the ladybird beetle Coleomegilla maculata (DeGeer). We also tested the hypothesis that C . maculata females must touch or taste DHBA to stimulate oviposition. We setup bioassays in communal cages (housing 10 females) and solitary cages (housing 1 female). In communal cages, nearly all egg clutches were found in or near the chemical dish with DHBA only. Provisioning cages with a tissue substrate reduced oviposition in the chemical dish. Regardless of oviposition site, egg number per clutch did not increase in communal cages or solitary cages with DHBA only. Affixing DHBA to the base of the chemical dish, then covering it with a nylon screen, reduced oviposition. This study suggests that females must touch or taste DHBA to stimulate oviposition. The physiological mechanism involved in oviposition stimulation requires further study. DHBA could potentially serve as a weak oviposition stimulant for predatory ladybird beetles in some mass-rearing systems.